Post-translational modifications of tubulin: pathways to functional diversity of microtubules - Song, Yuyu; Brady, Scott T. (Trends in cell biology, 2015)
•Tubulin modifications contribute to functional diversity of microtubules (MTs).•Post-translational modifications (PTMs) affect MT dynamics, organization, and interactions with other cellular components.•Various PTMs overlap or localize to specific MT domains demonstrating heterogeneity.•PTMs vary with time, cell type, subcellular compartment, and physiological state. Tubulin and microtubules are subject to a remarkable number of post-translational modifications. Understanding the roles these modifications play in determining the functions and properties of microtubules has presented a major challenge that is only now being met. Many of these modifications are found concurrently, leading to considerable diversity in cellular microtubules, which varies with development, differentiation, cell compartment, and cell cycle. We now know that post-translational modifications of tubulin affect, not only the dynamics of the microtubules, but also their organization and interaction with other cellular components. Many early suggestions of how post-translational modifications affect microtubules have been replaced with new ideas and even new modifications as our understanding of cellular microtubule diversity comes into focus.